2020
DOI: 10.1021/acs.langmuir.0c00507
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of an α-Gel (α-Form Hydrated Crystal) Induced by Temperature and Shear Flow in an Oleic Acid Based Gemini Surfactant System

Abstract: We studied the effects of temperature and shear flow on the structures of α-gel bilayers and domains. The α-gel samples were prepared by a carboxylate-type gemini surfactant synthesized from oleic acid and a long-chain alcohol (1-tetradecanol) with water. The structural change as a function of temperature was investigated using small-and wide-angle X-ray scattering (SWAXS) measurements, spin−spin relaxation time (T 2 ) measurements, and optical microscopy observations. SWAXS measurements suggested that the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(51 reference statements)
2
5
0
Order By: Relevance
“…Similar inflection points were observed previously in the α-gel system . Recently, we performed simultaneous small-angle neutron scattering and rheological (Rheo-SANS) measurements in an α-gel system consisting of an anionic gemini surfactant, 1-tetradecanol, and water . In this earlier work, we found that the bilayer structure remained even at high shear rates .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Similar inflection points were observed previously in the α-gel system . Recently, we performed simultaneous small-angle neutron scattering and rheological (Rheo-SANS) measurements in an α-gel system consisting of an anionic gemini surfactant, 1-tetradecanol, and water . In this earlier work, we found that the bilayer structure remained even at high shear rates .…”
Section: Resultssupporting
confidence: 85%
“…36 In this earlier work, we found that the bilayer structure remained even at high shear rates. 36 It seems, therefore, that the inflection points result from a change in the domain-to-domain network structure, although the exact mechanism for the observed behavior is not clear at present.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…22)) indicates that a lot of water is trapped between the lamellar bilayers, similar to the previous reports. 14,25,26 Based on the above results along with our previous work, 22 it can be concluded that, microscopically, a concentration-driven stepwise aggregation occurs in the KOCOOH solution (Fig. 5).…”
Section: Structure Of Aggregatessupporting
confidence: 70%
“…For instance, a family of lysine-based surfactants formed a range of tubule structures below their Krafft points (Tk = 25 -49 o C depending on surfactant architecture); however, a tubule-to-vesicle transition was observed as the temperature was increased [24]. Of specific relevance to gelation, the transition between a lamellar liquid-crystalline phase and an -gel phase was observed at T ~ 40 o C as a ternary gemini surfactant (synthesised from oleic acid), 1-tetradecanol, and water system was cooled [25].…”
Section: Introductionmentioning
confidence: 99%